O aquecimento e o desaquecimento vocal na arte do canto - Marques, Lúcia Sofia Serrano (2022)
Este trabalho consiste na elaboração do Relatório Final do Estágio de Ensino Supervisionado de música, que foi realizado como parte integrante e conclusiva do Mestrado em Ensino de Música, Canto Lírico da Escola de Artes da Universidade de Évora. A prática de Ensino Supervisionada desenvolveu-se no Conservatório Regional de Évora (EBORAE), no ano letivo de 2020/2021 tendo como objetivo primordial a consolidação e integração dos conhecimentos teóricos adquiridos no 1ºe 2º semestre do Curso de Mestrado, através da prática da docência supervisionada e orientada, com vista à profissionalização de professores competentes de ensino especializado da música. O presente relatório está estruturado em duas grandes partes: na primeira parte serão apresentadas as problemáticas das atividades desenvolvidas na prática de ensino supervisionada, o que foi trabalhado com os diferentes alunos e os métodos de ensino aplicados. A segunda parte é constituída pela pesquisa da temática escolhida, neste caso o Aquecimento e o Desaquecimento Vocal, como é visto pelos profissionais da voz, a sua problemática e importância para a vida profissional e de que forma este foi integrado e trabalhado ao longo do ano letivo no estágio; Abstract: Title: Vocal warm-up and cool-down in the art of singing This dissertation involves the elaboration of a supervised music internship report. This was accomplished to meet the criteria, that are mandatory, to conclude the masters in teaching program provided by Évora’s University School of Arts. The internship took place at Évora’s regional conservatory, Eboæ Mvsica (CREV), during the school year of 2020/21. The primary goal was to practice, in a supervised environment, some of the methodologies learned in the subjects provided during the 1st and 2nd semester of the Master’s program, which was designed to form competent individuals that are prepared to teach in specialized music schools. This dissertation is divided into two parts, the first part being the report of the internship where a description of all the activities done with the students will be provided, analyzing what was worked on, what methodologies were used and what problems were encountered. The second part is where I will focus in the research elaborated on the theme chosen, the importance of the vocal warning and cooling exercises. It will be discussed how voice professionals perceive the importance of this theme and it’s influences in every singer professional life. Different exercises will be described and explained by the results provided of its usage during the internship done during a year.